LEGAL ANALYSIS OF MEN LOOKING AT WOMEN IN THE BOOK KIFAYATU AL-AKHYAR BY IMAM TAQIYUDDIN AL HUSAINI - Embrizal Embrizal; Arsal Arsal (Adisam Publisher, 2026)
This study discusses the law of men looking at women in the perspective of the Kitab Kifayatu al-Akhyar by Imam Taqiyuddin al-Husaini, one of the great scholars of the Shafi'i school whose works are often used as references in the study of fiqh. This problem has a high urgency given that interaction between men and women in social life is inevitable, while Islamic sharia sets certain limits to maintain honor and prevent slander. This research aims to analyze the concepts, legal classifications, and basics of istinbath used by Imam Taqiyuddin al-Husaini in establishing the law of seeing women. This research is a library research with a normative-juridical approach. The main source of data is Kitab Kifayatu al-Akhyar fi Halli Ghayati al-Ikhtishar, while the supporting data sources come from the fiqh books of the Shafi'i school and relevant scientific literature. The data collection technique was carried out through documentation studies, while the data analysis used a descriptive-analytical method. The results of the study show that Imam Taqiyuddin al-Husaini divides men's views of women into several categories of law based on the existence or absence of the need and the potential for slander. Basically, seeing ajnabiyah women without a need that is justified by sharia is haram. However, in certain conditions such as the purpose of marriage and other shari'i needs, viewing is allowed with strict restrictions. This provision reflects the balance between legal strictness and benefit, and is relevant as a guideline for social ethics in the life of the Muslim community.